A new species of Liophloeothrips (Thysanoptera, Phlaeothripidae) from leaf litter from Iran - Hakimara, Mahsa; Minaei, Kambiz; Sadeghi, Saber; Mound, Laurence (Zootaxa, 2019)
Of the 16 species listed in the genus Liophloeothrips (ThripsWiki 2018), 13 are known only from India, and all of these are phytophagous with some inducing galls in various plant families (Tyagi & Kumar 2011). However, the biology of the type species, L. glaber, as well as that of the other two species, L. hungaricus and L. pulchrisetis, remains in doubt. Each of these three species is from Europe, with L. pulchrisetis known from a single female, L. glaber from two specimens, and hungaricus recorded from Hungary, Finland and Iran on a very few individuals (Minaei & Mound 2014). The record of L. hungaricus from Iran was published without any information concerning the locality, date of collection, or number of specimens (Mortazawiha 1995). However, Minaei and Mound (2014) pointed out that the slide label data of L. hungaricus specimens from Europe suggested that this species is associated with the bark of certain Salicaceae. Moreover, they indicated the possibility that the three names might actually represent a single species, although the male of L. glabrus has a sternal pore plate whereas this is apparently absent in hungaricus. Given the few known specimens, it is not possible to know if these thrips live under bark and feed on fungal hyphae, or if the few specimens collected were actually leaf-feeders that were sheltering under bark. In this paper, a new species of the genus is described from southern Iran, based on both sexes. These specimens were extracted from leaf litter using a Berlese funnel, thus again it is not possible to be certain if the species is part of the community of fungus-feeding litter thrips, or if the specimens were merely sheltering.